2019
DOI: 10.1016/j.memsci.2019.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Defect-free outer-selective hollow fiber thin-film composite membranes for forward osmosis applications

Abstract: This study presents the successful fabrication of a novel defect-free outer-selective hollow fiber (OSHF) thin-film composite (TFC) membrane for forward osmosis (FO) applications. Thin and porous FO membrane substrates made of polyether sulfone (PES) with a dense and smooth outer surface were initially fabricated at different air-gap distances. A modified vacuum-assisted interfacial polymerisation (VAIP) technique was then successfully utilised for coating polyamide (PA) layer on the hollow fiber (HF) membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 46 publications
(76 reference statements)
0
27
0
Order By: Relevance
“…PVP 4,29–31 and PEG as pore former are the most widely used additives used in FO membranes synthesis. Although addition of hydrophilic PEG into the dope solutions can improve pore formation and interconnection by producing a sponge‐like porous morphology, 32 but our pre‐tests revealed that the membrane fabricated by PEG 400 and PC was mechanically too weak and powdery. As a result, in this study PVP was selected as pore former.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…PVP 4,29–31 and PEG as pore former are the most widely used additives used in FO membranes synthesis. Although addition of hydrophilic PEG into the dope solutions can improve pore formation and interconnection by producing a sponge‐like porous morphology, 32 but our pre‐tests revealed that the membrane fabricated by PEG 400 and PC was mechanically too weak and powdery. As a result, in this study PVP was selected as pore former.…”
Section: Methodsmentioning
confidence: 80%
“…The pure water flux for the PC substrate was remarkably higher than that of the PES substrate. The pure water flux depends on the bulk porosity, surface porosity, and pore size due to the Hagen‐Poiseuille pore flow model 32 as well as the hydrophilicity of the substrates 27 . Water permeability and other characteristics of the substrates are also represented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the unique preparation procedure of PA-based membranes via interfacial polymerization on the porous support layer allows for a very thin selective layer formation, which results in much higher water permeability than the CTA-based membrane. On the other hand, at the same time, the two-step membrane preparation procedure of a PA-based membrane (porous support layer preparation and subsequent interfacial polymerization) might impede the mass production of the PA-based membrane applicable for the HF configuration, especially the outer-selective layer type of the PA-based membrane [ 67 ]. Although the CTA-based membrane has lower water permeability than the PA-based membrane, the simple preparation procedure of the CTA-based membrane allows for a HF configuration and a more highly effective membrane area compared to the PA-based membrane.…”
Section: Features Of Cta-hf Ro Modulementioning
confidence: 99%
“…It was found that VFA rejection by FO membrane was highly pH dependent and at pH 7.5 rejection rates above 80% was achievable. Lim, Tran, Tran, Akther, Phuntsho, and Shon (2019) successfully fabricated a defect-free outer-selective hollow fiber (OSHF) thin film composite (TFC) membrane for FO applications. This OSHF TFC membrane was found to achieve significant improvements on commercial FO membranes in water flux, specific reverse solute flux, fouling resistance, and cleaning efficiency.…”
Section: Annual Literature Reviewmentioning
confidence: 99%